2020
DOI: 10.1101/2020.07.20.20156398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and laboratory evaluation of patients with SARS-CoV-2 pneumonia treated with high-titer convalescent plasma: a prospective study

Abstract: Background Effective antiviral therapy against the severe acute respiratory syndrome virus 2 (SARS-CoV-2) remains elusive. Convalescent plasma is an anti-viral approach currently under investigation. We aimed to assess the laboratory and clinical parameters of patients with COVID-19 pneumonia treated with convalescent plasma containing high levels of neutralizing anti-SARS-CoV-2 antibodies.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Some significant concerns have been raised concerning the side effects of convalescent plasma in COVID-19, such as transfusion-associated circulatory overload, the infusion of complement proteins and coagulation factors to circulatory system and antibody-dependent enhancement of COVID-19 disease [ 35 ]. However, few adverse effects were observed with convalescent plasma transfusion in patients with severe and critical disease, according to publications included in our study [ 8 , 11 , 18 21 , 23 25 , 27 , 29 , 33 , 34 , 36 ]. A study of 5000 hospitalized patients with severe or life-threatening (critical) COVID-19 in the U.S. [ 16 ] reported that the incidence of all serious adverse events (SAEs) in the first four hours after transfusion was <1% and the rate of SAEs definitely associated with transfusion was objectively <0.1% of all transfusions.…”
Section: Resultsmentioning
confidence: 59%
“…Some significant concerns have been raised concerning the side effects of convalescent plasma in COVID-19, such as transfusion-associated circulatory overload, the infusion of complement proteins and coagulation factors to circulatory system and antibody-dependent enhancement of COVID-19 disease [ 35 ]. However, few adverse effects were observed with convalescent plasma transfusion in patients with severe and critical disease, according to publications included in our study [ 8 , 11 , 18 21 , 23 25 , 27 , 29 , 33 , 34 , 36 ]. A study of 5000 hospitalized patients with severe or life-threatening (critical) COVID-19 in the U.S. [ 16 ] reported that the incidence of all serious adverse events (SAEs) in the first four hours after transfusion was <1% and the rate of SAEs definitely associated with transfusion was objectively <0.1% of all transfusions.…”
Section: Resultsmentioning
confidence: 59%
“…Following removing duplicates and screening of titles and abstracts, we evaluated 153 articles in full text. Among these, we found 45 relevant articles (4RCTs, 11 controlled NRSIs, 7 non-controlled NRSIs and 23 case reports) [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Extracted details are presented in Table 1 (RCTs, controlled NRSIs, and non-controlled NRSIs) and table 2 (case report(series)).…”
Section: Resultsmentioning
confidence: 99%
“… No serious AEs. Donato et al [28] USA Prospective controlled study, SC Intervention 47; control 1340 Moderate-critically ill 500 ml(n = 36); 400 ml(n = 10); 200 ml(n = 1) Median time 8–15 days IgG Spike RBD > 1:500 HCQ,AZM,Steroids,Tocilizumab,Remdesivir CPT was safe and conferred effective transfer of immunity while preserving endogenous immune response Mild rash(n = 1) Ralph Rogers et al [29] USA A matched cohort analysis,SC Intervention 64,control 177 Severe ill One or two units 7 days after symptom onset SARS-CoV-2 IgG antibody index >1.4 Remdesivir, corticosteroids No overall significant reduction of in-hospital mortality or increased rate of hospital discharge associated with the use of CP in this study, although there was a signal for improved outcomes among the elderly. Two patients who received CP were judged to have a TRALI reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations